What Deters Child Sex Offenders? A Comparison Between Completed and Noncompleted Offenses. Issue 20 (October 2019) - Wortley, Richard; Leclerc, Benoit; Reynald, Danielle M.; Smallbone, Stephen
This study examined the role of the reaction of the victim, the nature of the physical setting, and the proximity of third parties in deterring offenders from completing an act of child sexual abuse (CSA). A self-report study was conducted with 238 adult males serving a custodial sentence for CSA, of whom 82 identified an occasion in which they had tried to have sexual contact with a child but did not because they were stopped or discouraged. We examined the situational characteristics of the noncompleted offense and compared these with the most recent completed offense by the same offenders. The most common reason for stopping the noncompleted offense, given by more than half of the participants, was the negative reaction of the child, and in particular, the direct request by the child to stop. Actual or potential actions by third parties were the next most cited reasons, with around a quarter of cases stopped because the offender was interrupted. In comparison to the noncomplete offense, in the completed offense the child was more likely to be younger and to be perceived as a willing participant. The most common suggestion for what might have stopped the completed offense, endorsed almost universally, was a negative reaction from the child. Factors that increased the chance of being detected—someone being nearby and the possibility of being observed—were also strongly endorsed. We argue that the findings provide the basis for devising offense-focused prevention strategies for CSA.